Fluorine-18 labelled prostate-specific membrane antigen (PSMA)-1007 positron-emission tomography–computed tomography: normal patterns, pearls, and pitfalls. Issue 12 (December 2020) - Foley, R.W.; Redman, S.L.; Graham, R.N.; Loughborough, W.W.; Little, D.
Abstract : Prostate-specific membrane antigen (PSMA)-based positron-emission tomography (PET)-computed tomography (CT) has shown great promise in prostate cancer imaging. This technique has demonstrated particular utility in the staging of high-risk primary cancer and in the localisation of recurrent disease. The use of fluorine-18 PSMA-1007 is advantageous, as it is excreted via the hepatobiliary system rather than urinary and the longer half-life of fluorine-18 compared to gallium tracers, allows for PSMA imaging in centres without a gallium generator. However, imaging with this tracer is not without flaws and areas of ambiguity remain. In this article, the biodistribution, clinical indications, and pearls of 18 F-PSMA-1007 PET-CT in patients with prostate cancer will be discussed, as well as the potential pitfalls in the reporting of these studies. Highlights: Fluorine-18 PSMA-1007 is a novel PET-CT radiotracer. It can be used to localise sites of recurrent prostate cancer. It may also be used in the staging of high risk prostate cancer. This review exhibits the clinical utility of Fluorine-18 PSMA-1007 PET-CT. We also illustrate the important pitfalls of this imaging technique.